Recent Developments in Modeling and Applications in Statistics - Oliveira, Paulo Eduardo (Springer, 2013)
Sampling and Modeling -- Estimation -- Extremes -- Testing Statistical Hypothesis -- Models with Stochastic Differential Equations -- Stochastic Processes. .
Description based upon print version of record
Keywords: Konferenzschrift -- 2010 -- São Pedro do Sul, Portugal; Statistik